The influence of different conflict management styles on depressive symptoms in employees: the mediating role of emotional exhaustion - Zhang, Qihan; Lin, Yueran; Zhang, Yimou; Yang, Shaofeng (Frontiers in Public Health, 2024)
Although some studies have found that conflict management styles impact employees' levels of depression, the expressions of employees' depressive symptoms under various conflict management styles and the underlying mechanisms remain to be elucidated. In this study, a total of 1,312 employees were gathered through an online survey to examine their current depressive status. Drawing on the conservation of resources theory, the mediating role of emotional exhaustion in the association between conflict management style and employee depression was further explored. The findings revealed that the prevalence of moderate to severe depression among the workers was 13.9%. Employees with different conflict management styles displayed distinct depression scores. The high coordination style group exhibited a significantly lower depression score compared to the high concession style group. Emotional exhaustion played a mediating role in the impact of both the coordination style and the concession style on employees' depression. It can be seen that the mental health needs of the workplace are imminent. The intervention measures to improve the mental health of employees in the working environment should take into account the cultivation of the coordination style of employee conflict management, reduce their emotional exhaustion, and stay away from depression through the acquisition of constructive and positive coping styles.